Bridging Gaps in Mental Health Care Through Music Therapy: A Narrative Review - Nazaruddin, M. Arief; Mahfudzi, Aan (Indonesian Scientific Publication, 2025)
Music therapy has gained increasing recognition as a non-pharmacological intervention for improving mental health in both clinical and community settings. This narrative review aimed to synthesize current evidence on its effectiveness, methodological approaches, and systemic challenges. Literature was systematically identified through major databases including PubMed, Scopus, and Google Scholar, using keywords such as